Community Characteristics of Sympatric Freshwater Turtles from Savannah Waterbodies in Ghana - Gbewaa, S.B.; Oppong, S.K.; Horne, B.D.; Tehoda, P.; Petrozzi, F.; Dendi, D.; Akani, G.C.; Vittorio, M. di; Ajong, S.N.; Pacini, N.; Fa, J.E.; Luiselli, L. (Springer, 2021)
Despite increasing pressures on freshwater resources worldwide, and the threatened status of most freshwater turtles, there is still limited knowledge of habitat use and niche partitioning in Afrotropical freshwater turtle communities. In this study, we describe habitat associations, community diversity, and temporal patterns of occurrence of freshwater turtle species in the Dahomey Gap ecoregion of Ghana (West Africa). We gathered data from 13 sites in central Ghana and along the Sene Arm of Lake Volta in the Digya National Park (Bono East Region). We employed opportunistic short-term surveys (at seven sites) together with longer-term (six-months duration) standardized evaluations of turtle presence and numbers in different habitats (at six sites). Overall, a total of 210 turtle individuals of four species (Trionyx triunguis, Cyclanorbis senegalensis, Pelomedusa sp. and Pelusios castaneus) were recorded; precise capture sites and habitat type were recorded for 139 individuals, but the 71 individuals observed in marketplaces were not considered in our analyses. At a local scale, we observed three sympatric species in various study sites. In each of these sites, the dominant species was either C. senegalensis or Pelomedusa sp., with the latter species being more abundant in temporary waterbodies and C. senegalensis more numerous in permanent ones. A Multiple Correspondence Analysis suggested that, in permanent waterbodies all species were associated with similar physical habitat variables. In a Canonical Correspondence Analysis, we showed that the density of herbaceous emergent vegetation was more important for P. castaneus than for C. senegalensis. Comparisons of diversity metrics between our study sites and previous studies revealed that turtle community composition was similar across savannah sites.